Построение (min, max)-эквивалентных ч. у. множеств - Бондаренко, В.М.; Степочкина, М.В. (Інститут математики НАН України, 2009)
In this paper we solve the problem on an explicit construction of a (min, max)-equivalent partially ordered set for given defining sequences.